2014
DOI: 10.1021/bc500083t
|View full text |Cite
|
Sign up to set email alerts
|

Cell Labeling via Membrane-Anchored Lipophilic MR Contrast Agents

Abstract: Cell tracking in vivo with MR imaging requires the development of contrast agents with increased sensitivity that effectively label and are retained by cells. Most clinically approved Gd(III)-based contrast agents require high incubation concentrations and prolonged incubation times for cellular internalization. Strategies to increase contrast agent permeability have included conjugating Gd(III) complexes to cell penetrating peptides, nanoparticles, and small molecules which have greatly improved cell labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…32 Herein, we incorporate lipophilic contrast agents 1 and 2 into nanodiscs to generate water-soluble, multimodal, and modular platforms for cellular imaging (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Herein, we incorporate lipophilic contrast agents 1 and 2 into nanodiscs to generate water-soluble, multimodal, and modular platforms for cellular imaging (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…32 Monomeric 2 was synthesized according to Scheme S1. Specifically, 2-decyltetradecan-1-ol was brominated with NBS to yield 11-(bromomethyl)tricosane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed ionic relaxivities decrease to 4.7 ± 0.3 mM −1 s −1 for 1 and 5.2 ± 0.3 mM −1 s −1 for 2 at 7 T and are consistent with values obtained from agents generated from similar scaffolds. 20,21 …”
mentioning
confidence: 99%
“…Our lab continued the development of lipophilic contrast agents by comparing the labeling and retention of monomeric (contains one Gd(III) complex) and multimeric (contains three Gd(III) complexes) agents. [21] We showed that the monomeric agent had the surprising ability to label cells more effectively and produce more significant contrast enhancement of cells than its multimeric counterpart. Further, the monomeric agent had improved solubility and did not require incubation with detergent in biological media, a limitation of the multimeric design.…”
Section: Introductionmentioning
confidence: 99%